Effects of dietary menthol on growth performance and antioxidant, immunological and biochemical responses of rainbow trout (Oncorhynchus mykiss) - Seyyed Morteza Hoseini (2020)
© 2020 The present study aimed to investigate the effects of dietary menthol administration on growth performance and antioxidant, immunological and biochemical responses of rainbow trout (Oncorhynchus mykiss). For this, the fish were fed with diets supplemented with 0 (CTL), 0.11 (0.1 M), 0.25 (0.25 M) and 0.5 (0.5 M) % menthol for 60 days. Then, the fish growth performance, and body proximate composition, blood RBC, plasma stress, antioxidant, enzymatic and immunological responses were determined. Dietary menthol administration had no significant effects on the fish growth performance, body composition and plasma cortisol, glucose, total immunoglobulin and complement levels. Dietary menthol (0.25 M and 0.5 M) significantly increased plasma superoxide dismutase, catalase, total antioxidant capacity, RBC, total protein, globulin, lysozyme and bactericidal activity against Aeromonas hydrophila. These treatments significantly decreased plasma malondialdehyde, aspartate aminotransferase and alkaline phosphatase. In conclusion, menthol triggers antioxidant system and prevents hemolysis. Moreover, menthol improved some innate immune components and antibacterial effects of the fish plasma against an important aquatic pathogen. Dietary menthol administration at 0.25–0.5% is suitable to enhance antioxidant and immune strength in rainbow trout, without negative effects on the fish growth performance.